Promotion of Crypt-like Structures in Intestinal Organoid Development through the Addition of Graphene Oxide in Cell-based Assays - Sulaksono, Haura Labibah Salsabil; Kamilah, Mutiara Mila; Faridah, Lia; Joni, I Made; Watanabe, Kozo; Ekawardhani, Savira (Universitas Islam Bandung, 2024)
The intestinal organoid represents a miniature organ that can mimic functional physiology and pathology. However, there are several challenges to developing the organoid system, such as the limited survival of cells. Based on theory, matrix addition is a factor that can support survival in cells. As a result, graphene oxide (GO) addition is used in this study. As an artificial matrix, GO has been successfully shown to encourage good cell behavior and is well known for having good biocompatibility. Herein, we fabricate GO characterized with FT-IR and PSA. Crypt-like structures (CLS) are isolated from small intestinal mice in GO addition as a matrix. The gene expression and cell viability of CLS are investigated. RT-PCR examined the gene expression in CLS, while cell viability of CLS was carried out using the staining method. This study was conducted at FiNder U-CoE and Parasitology Laboratory of HSE Universitas Padjadjaran Bandung during February and December 2023. Our results show that Vil-1 as an identity for cells in the intestinal epithelium has been expressed in CLS primary significantly higher than intestinal tissue (p=0.01). However, identifying Lgr5 in CSL isolates is tricky. Thes in the crypt may be limited. Besides that, cell viability of CLS with GO addition can be maintained for four days. The GO addition as a matrix may provide support to maintain CLS. These findings are promising as cell-based assays for developing organoid models.